Mechanisms and Clinical Assessment of Fear of Disease Progression in Amyotrophic Lateral Sclerosis - Ting Wang; Tao Jin; Zhuoyuan Cai; Zhen Yan (Discovery Medicine, 2026)
Amyotrophic lateral sclerosis (ALS) is a progressive, life-limiting neurodegenerative disease characterized primarily by motor dysfunction, although cognitive and behavioral impairment occurs in a substantial subset of patients. Progressive functional decline and prognostic uncertainty may contribute to pronounced fear of disease progression (FoP). Increasing evidence suggests that FoP represents a distinct psychological response to the expected functional loss related to disease, rather than merely a secondary manifestation of ALS symptoms. To clarify the potential biological basis of ALS-related FoP, this review synthesizes current evidence regarding stress hormone pathways, autonomic nervous system (ANS) dysfunction, inflammation, and the gut-brain axis. Based on the available evidence, we propose that FoP may emerge from persistent mismatch between patients’ perceived disease-related threats and their adaptive capacity to these challenges. Multiple interacting systems may contribute to this process, including dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, autonomic imbalance, sleep and circadian rhythm disruption, peripheral and central inflammatory responses, and changes in the gut microbiota that may influence emotional regulation and physical symptoms. These interacting processes may create a reinforcing cycle: ALS-specific pathological features may enhance FoP, while the neuroendocrine mechanisms associated with FoP may further aggravate the severity and burden of the disease, thereby increasing the complexity of disease management. Future studies should prioritize the development of molecular biomarkers, as these biomarkers may provide valuable guidance for establishing ALS-specific FoP assessment tools and developing novel therapeutic strategies.